On the Quest for Authentic Christianity: Protestant Tradition and the Mission of Jesus - Ruthven, Jon (Journal of pentecostal theology, 2016)
Barth’s dream of a Spirit-centered theology hints at the great disconnect between the New Testament portrayal of the mission and message of Jesus and the ‘gospel’ of traditional Protestantism. This disconnect appeared as a result of the Reformers’ adoption of cessationism to undercut Papal authority, which rested, in part, on the idea of continuing revelation and miracle. The failure of both sides to understand the purpose of charismatic revelation and power as the central characteristic of the New Covenant, resulted in a misunderstanding of the mission of Jesus, the purpose of the cross, and the continuing commission of Christian disciples. In this, traditional theology significantly distorted the Christian message away from that of Jesus and the New Testament witness—a gospel about Jesus rather than from Jesus.